2018
DOI: 10.1111/1758-2229.12680
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and biogeography in Arctic soils

Abstract: Microorganisms dominate terrestrial environments in the polar regions and Arctic soils are known to harbour significant microbial diversity, far more diverse and numerous in the region than was once thought. Furthermore, the geographic distribution and structure of Arctic microbial communities remains elusive, despite their important roles in both biogeochemical cycling and in the generation and decomposition of climate active gases. Critically, Arctic soils are estimated to store over 1500 Pg of carbon and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 122 publications
(155 reference statements)
10
69
0
1
Order By: Relevance
“…At the VC permafrost tunnel, archaeal diversity was dominated by the Soil Crenarchaeotic Group (SCG; Thaumarchaeota ; up to 70.9% relative abundance) and Methanosarcinales (up to 52.6% relative abundance). Prior studies have also found large abundances of Methanomicrobia in Alaskan soils (Malard & Pearce, ). Methanogens have also been detected in buried yedoma permafrost in northeast Russian (Bischoff et al, ; Rivkina et al, ) and the CRREL permafrost tunnel in Fox, AL (Mackelprang et al, ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…At the VC permafrost tunnel, archaeal diversity was dominated by the Soil Crenarchaeotic Group (SCG; Thaumarchaeota ; up to 70.9% relative abundance) and Methanosarcinales (up to 52.6% relative abundance). Prior studies have also found large abundances of Methanomicrobia in Alaskan soils (Malard & Pearce, ). Methanogens have also been detected in buried yedoma permafrost in northeast Russian (Bischoff et al, ; Rivkina et al, ) and the CRREL permafrost tunnel in Fox, AL (Mackelprang et al, ).…”
Section: Discussionmentioning
confidence: 80%
“…Following thaw, suitable conditions could allow for the activation of microbial communities, including methanogens, and subsequent GHG production (Knoblauch et al, 2018;Mackelprang et al, 2011;Wei et al, 2018). However, microbial communities in deep permafrost remain a relatively unknown component, and we cannot currently predict how microbes will use permafrost OC following thaw (Graham et al, 2012;Malard & Pearce, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We can also make ecological inferences using phylogenetic turnover (Cavender-Bares et al, 2009;Tripathi et al, 2018). Microbial diversity of extreme ecosystems, like Arctic soils, could be substantially different, while other non-extreme environments, for example, forest and agricultural fields, may harbour similar communities (Malard and Pearce, 2018). Long-term crop cultivation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant cyanobacterial orders in Arctic soil crusts were found to be the Nostocales, Oscillatoriales and Synechococcales (Steven et al ; Pushkareva et al ). Indeed, cyanobacteria are mainly responsible for the uptake of CO 2 and N 2 as plants in Arctic ecosystems are unable to fix nitrogen (Malard and Pearce ).…”
Section: Permafrost Soilsmentioning
confidence: 99%
“…Archaea have also been isolated from permafrost (Jansson and Taş ). Archaeal communities in Arctic soils seem to be variable through Methanobacteria and Methanomicrobia ( Euryarchaeota ) are abundant in Alaskan and Greenland soils (Ganzert et al ; Malard and Pearce ), whereas isolates related to the genera Methanolobus and Methanomethylovorans have been recovered from frozen ground in the Zoige wetland of the Qinghai—Tibet plateau (Zhang et al ). The methane released by these organisms can be used as a sole carbon source by methanotrophic bacteria, such as α‐ and γ‐proteobacteria (Coolen et al ) and members of the Methanococcales (Martineau et al ).…”
Section: Permafrost Soilsmentioning
confidence: 99%